URGENSI APARAT DESA ATAS STATUS HAK PENGUASAAN TANAH WAKAF PEMAKAMAN OLEH MASYARAKAT - HAMID, MOHAMAD RINALDI (Ganec Swara, 2025)
This study aims to analyze the urgency of the role of village officials in managing the status of land ownership rights for burial waqf by the community. Land has a very important role in human life, as a source of needs and a place for various activities. In Indonesia, land is not only an element of social and economic life, but also part of agrarian law regulated by Law Number 5 of 1960 concerning the Principles of Agrarian. Waqf land, which is used for religious and social purposes, is a subject that requires clear and precise management, especially in terms of ownership rights status. Although positive law and Islamic jurisprudence provide guidance regarding the management of waqf land, the problem that often arises is the unclear management and ownership rights status of burial land by the community. In this case, village officials play an important role in regulating and ensuring legal certainty over the land, so as to prevent disputes and facilitate the social and religious interests of the community. This study aims to analyze the urgency of the role of village officials in managing the status of land ownership rights for burials and provide recommendations regarding regulations that must be made to maintain legal certainty. The method used is a normative approach, by analyzing applicable legal regulations and their implementation at the village level.